The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/fst.101922
|View full text |Cite
|
Sign up to set email alerts
|

The anti-oxidative capacity of fermented lemon peel and its inhibitory effects on Lipopolysaccharide (LPS)-induced RAW 264.7 cell inflammatory response and cell apoptosis

Abstract: Chronic inflammation plays a key role in the development and progression of several chronic diseases. Inhibiting the inflammatory cascade, thereby minimising the damage caused by the inflammatory mediators, can be one of the strategies in chronic disease management. In addition, inflammation is closely related to apoptosis, and inflammation can cause apoptosis. Lemon peel has been reported to have antioxidant and anti-inflammatory biological activities. This study aimed to investigate the antioxidant activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…During infection, trauma, and tissue damage, IL-6 production increases, promoting immune cell activation and infammatory responses [32]. Based on multiple research fndings, it has been shown that LPS has an impact on RAW 264.7 cells and splenocytes by increasing the levels of infammatory cytokines, including TNF-α, IL-1β and IL-6 [4,5,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…During infection, trauma, and tissue damage, IL-6 production increases, promoting immune cell activation and infammatory responses [32]. Based on multiple research fndings, it has been shown that LPS has an impact on RAW 264.7 cells and splenocytes by increasing the levels of infammatory cytokines, including TNF-α, IL-1β and IL-6 [4,5,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Then, 100 µL of 1N NaOH was added, the mixture was heated to 37 • C for 60 min, and the absorbance was measured at 420 nm. The flavonoid content was calculated from the standard calibration curve obtained using Quercetin (Sigma-Aldrich Co., St. Louis, MO, USA) as the reference (standard concentration is 0-1280 µg/mL) to draw the standard curve [22].…”
Section: Assessment Of the Total Flavonoid (Tf) Contentmentioning
confidence: 99%